(untitled) (gjstudies, 2025)
This research investigates the underexplored bidirectional causality between capitalstructure decisions and accounting policy selection, moving beyond the traditional unidirectional frameworks that dominate corporate finance literature. We propose a novelmethodological approach by integrating agent-based modeling with historical corporatedata analysis to simulate how firms simultaneously optimize financing strategies andaccounting choices under conditions of market uncertainty and regulatory constraints.Our model treats accounting policy not merely as a reporting outcome but as a strategic variable that actively shapes and is shaped by leverage targets, debt covenants, andequity market perceptions. The study formulates three unconventional research questions: (1) How do firms dynamically co-adapt capital structure and accounting policiesin response to evolving market conditions? (2) What strategic equilibria emerge whenaccounting flexibility is explicitly modeled as a component of financial strategy? (3)How do information asymmetries between managers and capital providers create feedback loops between reporting choices and financing decisions? We develop a multi-agentsimulation framework where heterogeneous firms interact within a simulated capitalmarket, making simultaneous decisions about debt-equity mixes and accounting policyselections from permissible alternatives. The model incorporates learning mechanismswhere firms adjust strategies based on observed outcomes of peer entities. Our analysis of simulated data reveals several counterintuitive findings: firms often convergetoward suboptimal capital structures when accounting policy selection is treated asexogenous rather than endogenous; moderate accounting conservatism correlates withmore stable leverage ratios during market downturns; and strategic complementaritiesexist between certain accounting methods and specific financing instruments that areoverlooked in conventional models. The results demonstrate that treating accounting policy as an integrated component of capital structure strategy leads to differentnormative prescriptions than traditional sequential models. This research contributesoriginal insights by reframing the relationship between financing and reporting decisions as a simultaneous optimization problem, offering a more holistic understanding ofcorporate financial strategy formulation. The findings have implications for financialregulation, corporate governance, and the design of managerial incentive systems thatrecognize the interconnected nature of these fundamental business decisions.